Features of of metabolic indicators in pregnant cows during late prenatal period - O. V. Sokolova; M. N. Isakova; M. V. Ryaposova (Аграрная наука Евро-Северо-Востока)
The article presents data on the study of the characteristics of the biochemical profile in pregnant cows at late gestation. The research was carried out in agricultural organizations of the Sverdlovsk Region. Deviations of mean values of globulin content (47.0±1.2 g/l), total creatine phosphate kinase (310.1±55.4 U/l), triglycerides (0.4±0.1 g/l), magnesium (1.3±0.1 mmol/l) in the group of deep-bodied cows were in the direction of increase in indices. An increase in the total protein content of more than 82 g/l was observed in 37.2% of the cows examined, a decrease in the albumin concentration of less than 29 g/l in 13.2%, a urea level of less than 2.0 mmol / L in 20.7% and aminotransferases (ALT And ASAT) in 1.0.23.1% of deep-bodied cows, respectively. The revealed changes indicate a decrease in the processes of transamination and synthetic function of the liver, due to an increased functional load on the organ. A change in lipid metabolism was revealed, which manifested by an increase in cholesterol content of more than 5.0 mmol/l in 6.0% and triglycerides in 1.5.2 times in 25% of pregnant cows. The increase in activity of creatine phosphate kinase (CK) above 280 U/l was found in 16.9% of pregnant cows, which indicates an increase in the alakta mechanism of energy supply, and may be associated with a pronounced load on the cardiovascular system, an increase in the activity of CK in the placenta in its pathology. A physiological increase in lactate dehydrogenase and alkaline phosphatase was noted in 9.2% and 2.5% of the cows examined, respectively. There is metabolic change in acid-alkaline and water-electrolitic exchanges. At analysis of mineral metabolism indices it was pointed out decrease in calcium and phosphorus content in blood of 9.1 and 15.7 pregnated cows that is linked with increase in processes of ossification of embrion steleton and established of its haemopoesis. Hypokaliemie is recorded in 54.5% of cows. Analysis of results about content of microelements in blood of pregnated cows showed the increase in Zn and Cu content at 10.3 and 4.2% of animals. At this the deficite of these elements was indicated in 6.9 and 8.3% of cows.